Improving The Early Life Strength Of Cold Bituminous Emulsion Mixtures By Plastic Cells Reinforcement - I Nyoman Arya Thanaya (Jurnal Teknik Sipil, 2011)
Cold Bituminous Emulsion Mixtures (CBEMs) for road pavement are weak at their early life time because they still contain some amount of water. When it is necessary reinforcement on CBEMs is possible to improve the early life strength of the mixtures. The objective of the investigation was to find out the suitable position of the reinforcement on CBEMs in order to improve the early life strength of the mixture that can prevent early life failure. The reinforcement materials used was plastic cells which were made from standard extruded polyvinyl chloride (PVC) sheet. The plastic cells were positioned at the middle height and at the upper side close to the surface of the CBEMs samples. The samples were subjected to dynamic cylindrical loading, where the number of dynamic load applied and the deformation were electronically recorded. Stress and strain distribution was analyzed using BISAR 3.0 software from Shell company. It was found that the suitable position of the reinforcement on CBEMs is on the upper side (close to the surface), which gives significant prevention on deformation and crack during early age of CBEMs.